Towards the Integration of Complementary and Alternative Medicine: Dolphin-Assisted Therapy - Kreivinienė, Brigita; Acienė, Elvyra (Social Welfare: Interdisciplinary Approach, 2026)
The scientific article analyses the health care system of European countries and Lithuania in the context of complementary and alternative medicine. The article reviews the relationship between the traditions of conventional medicine and alternative and complementary medicine, patients’ attitudes towards the methods of complementary and alternative medicine, as well as dolphin-assisted therapy as one of the methods of complementary and alternative medicine. The impact on people with disabilities achieved by implementing the innovations of complementary and alternative medicine in the health system is reviewed. The aim is to investigate the links between conventional medicine and complementary and alternative medicine – specifically, dolphin-assisted therapy – through the impact on people with disabilities in implementing health system reforms. The research presents 147 interviews conducted with parents whose children with disabilities participated in dolphin-assisted therapy. The research data were processed by using qualitative content analysis. The research revealed that, from the point of view of parents raising children with disabilities, dolphin-assisted therapy is a health innovation that can be attributed not to complementary and alternative medicine, but rather to conventional medicine due to the complexity of the applied programme and methods. European Union countries treat complementary and alternative medicine methods in a different way, and the law adopted in Lithuania in 2020 opened opportunities for the development of conventional medicine and the regulation of complementary and alternative medicine, and the changes of health system reform expand the opportunities of integrative medicine for the choice of innovative methods for people with disabilities that affect the quality of life and better response to needs.